Fluid mechanics with engineering applications - Finnemore, E. John; Franzini, Joseph B. (The McGraw-Hill series in civil and environmental engineering, 2002)
This book is well known and well respected in the civil engineering market and has a following among civil engineers. This book is for civil engineers that teach fluid mechanics both within their discipline and as a service course to mechanical engineering students.